2023
DOI: 10.1002/smll.202207834
|View full text |Cite
|
Sign up to set email alerts
|

High‐Voltage Supercapacitive Swing Adsorption of Carbon Dioxide

Abstract: Supercapacitive swing adsorption (SSA) with garlic roots‐derived activated carbon achieves a record adsorption capacity of 312 mmol kg−1 at a low energy consumption of 72 kJ mol−1 and high mass loadings (>30 mg cm−2) at 1.0 V for 85%N2/15%CO2 mixtures. The activated carbons are inexpensively prepared in a one‐step process using potassium carbonate, and air as activators. The adsorption capacity further increases with increasing voltage. At a voltage of 1.4 V, a sorption capacity of 524 mmol kg−1 at an energy c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 28 publications
2
12
0
Order By: Relevance
“…In these experiments, the electrochemical cell was charged to a cell voltage of -0.8 V ("negative charging mode", the gas-exposed electrode is negatively charged) or + 0.8 V ("positive charging mode", the gas-exposed electrode is positively charged) with constant current charging (and discharging) and 5-min voltage holds between charge and discharge. Similar to previous studies, [16][17][18]22 CO2 capture is observed upon negative charging to -0.8 V (Figure 2C). Upon cell discharging back to 0 V CO2 release is then observed, with the behaviour repeatable over several cycles.…”
Section: Effects Of Electrode Charging Protocols On Electrochemical C...supporting
confidence: 90%
See 1 more Smart Citation
“…In these experiments, the electrochemical cell was charged to a cell voltage of -0.8 V ("negative charging mode", the gas-exposed electrode is negatively charged) or + 0.8 V ("positive charging mode", the gas-exposed electrode is positively charged) with constant current charging (and discharging) and 5-min voltage holds between charge and discharge. Similar to previous studies, [16][17][18]22 CO2 capture is observed upon negative charging to -0.8 V (Figure 2C). Upon cell discharging back to 0 V CO2 release is then observed, with the behaviour repeatable over several cycles.…”
Section: Effects Of Electrode Charging Protocols On Electrochemical C...supporting
confidence: 90%
“…Recent work has begun to optimise electrode materials, 18 electrolyte composition 19,20 and charging protocols. 17,21,22 Most notably, a recent study showed that activated carbon electrodes with higher electrochemical capacitances could achieve higher CO2 capture capacities and rates approaching 270 mmolCO2 kg -1 and 300 mmolCO2 kg -1 h -1 , respectively. 18 Despite this progress, it remains unclear how the specific electrode structure (e.g., surface area, pore size, surface functional groups, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…Our group reported an energy consumption of ≈100 KJ mol −1 with 78% energy efficiency using 7 cm BPL‐AC electrodes in 5 M NaCl and 1 M MgBr 2 electrolyte, arguing that improved energy consumption may be achievable by use of 5 M NaCl, or 1 M MgBr 2 . [ 57 ] More recently, we reported energy consumption values of ≈70 KJ mol −1 using hot‐pressed garlic‐roots derived electrodes, [ 58 ] arguing that development of new electrode materials is another promising route to further minimize the energy consumption values.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, it was found that appropriately increasing the charging voltage can increase the CO 2 adsorption capacity, but this will increase energy consumption, and excessive charging voltage will reduce capacitance performance. Li et al [72] employed the garlic roots activated carbon electrode, expanding the negative charging voltage from À 1.0 V to À 1.4 V, the energy consumption increased only slightly (130 kJ mol À 1 ), and a high CO 2 adsorption capacity of 461 mmol kg À 1 was achieved, which was greatly improved compared with the CO 2 adsorption capacity (312 kJ mol À 1 ) obtained from À 1.0 V negative charging, in addition to the high specific capacitance and stable SSA performances of the garlic roots activated carbon as shown in Figure 12(a). In the experiment with a gas flow rate of 5 sccm (standard cubic centimeter per minute), and a charging voltage from 0 to À 1.4 V a higher CO 2 adsorption capacity of 524 mmol kg À 1 was obtained as shown in Figure 12(b).…”
Section: Charging Protocolsmentioning
confidence: 99%